EVALUATION OF THE PHARMACOLOGICAL POTENTIAL OF CHINESE HERBAL MEDICINE - Bauer, R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Traditional Chinese medicine is based on thousands of years of experience and is based on a specific theory with a holistic approach for disease and health management. In order to evaluate the full pharmacological potential of Chinese herbal medicine it is necessary to consider the classical concepts of diagnosis and medication. The approach of systems biology is certainly best suited since it allows the broadest analysis of a metabolic status and of the effects of treatments. For the identification of the active principles metabolic transformation as well as synergistic effects must be considered. Also the rationale for the application of mixtures of herbs needs to be evaluated. Some recent examples of our research on Chinese herbs with anti-inflammatory and anti-cancer activity will be presented: From Centipeda minima (L.) A.Braun & Asch. (Asteraceae) we have isolated the sesquiterpene lactones 6-O-methylacrylplenolin, 6-O-angeloylplenolin and 6-O-tigloyl-plenolin, which exhibited strong inhibitory properties on inducible nitric oxide synthase (iNOS) in RAW 264.7 macrophages after stimulation by interferon-gamma and LPS [1]. From the fruits of Evodia rutaecarpa (Juss.) Benth. (Rutaceae), we have isolated the quinolinone alkaloids 1-methyl-2-nonyl-4(1H)-quinolinone, 1-methyl-2-(6Z)-6-undecenyl-4(1H)-quinolinone, 1-methyl-2-(4Z,7Z)-4,7-tridecadienyl-4(1H)-quinolinone, evocarpine and 1-methyl-2-(6Z,9Z)-6,9-pentadecadienyl-4(1H)-quinolinone, which showed strong inhibitory activity on leukotriene biosynthesis in human polymorphonuclear granulocytes [2]. Moreover they were very effective against mycobacteria [3]. They showed no cytotoxic activity and might bind to the lipid binding site of 5-LOX [4]. Extracts from Chinese herbs have been also screened for inhibition of expression of NF-kB1 in THP-1 cells by a new quantitative method based on real time PCR [5]. Overexpression of this transcription factor is associated with inflammatory diseases, like rheumatoid arthritis, atherosclerosis, asthma and inflammatory bowel disease. [1] Fischer, M., Kunert, O., Schmidt, K., Bauer, R. Sesquiterpene lactones from Centipeda minima with iNOS inhibitory activity. in preparation (2008). 2] Adams, M., Mahringer, A., Kunert, O., Fricker, G., Efferth, T., Bauer, R. Cytotoxicity and P-Glycoprotein Modulating Effects of Quinolones and Indoloquinazolines from the Chinese Herb Evodia rutaecarpa. Planta Med. 73, 1554-1557 (2007) [3] Adams, M., Kunert, O., Haslinger, E., Bauer, R. Inhibition of leukotriene biosynthesis by quinolinone alkaloids from the fruits of Evodia rutaecarpa. Planta Med. 70, 904 - 908 (2004). [4] Adams, M., Abebe Wubea, A., Kunerth, O., Haslinger, E., Bucar, F., Bauer, R. Quinolone alkaloids from Evodia rutaecarpa: A potent new group of antimycobacterial compounds. Int. J. Antimicrob. Agents 26(3), 262 -264 (2005).